2016
DOI: 10.1093/cercor/bhw394
|View full text |Cite|
|
Sign up to set email alerts
|

Neurexins 1–3 Each Have a Distinct Pattern of Expression in the Early Developing Human Cerebral Cortex

Abstract: Neurexins (NRXNs) are presynaptic terminal proteins and candidate neurodevelopmental disorder susceptibility genes; mutations presumably upset synaptic stabilization and function. However, analysis of human cortical tissue samples by RNAseq and quantitative real-time PCR at 8–12 postconceptional weeks, prior to extensive synapse formation, showed expression of all three NRXNs as well as several potential binding partners. However, the levels of expression were not identical; NRXN1 increased with age and NRXN2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 111 publications
2
49
0
Order By: Relevance
“…() and Harkin et al. (). Experimental studies have also shown that the distribution of diverse SP neurons conforms to the multiple functional roles of SP (Kanold, ; Khazipov & Luhmann, ; Luhmann et al.…”
Section: Discussionmentioning
confidence: 99%
“…() and Harkin et al. (). Experimental studies have also shown that the distribution of diverse SP neurons conforms to the multiple functional roles of SP (Kanold, ; Khazipov & Luhmann, ; Luhmann et al.…”
Section: Discussionmentioning
confidence: 99%
“…SVZ / VZ represents the subventricular and ventricular zones where the neurons and glial cells are generated; IM / PWM denotes the intermediate zone that gradually develops into the periventricular white matter; MZ is the marginal zone. The following three timelines represent from bottom to top: the hyperexcitability of the nervous system, in which the intensity of the grey shading represents the degree of hyperexcitability; the cortical network activity that emerges across the brain from 9 to 10 weeks PMA , this gradually increases (indicated by increasing shading) to be full‐blown present (in the subplate) at mid‐fetal age, before moving from global and widespread activity to local and limited activity (‘sparsification’, indicated by the diminution of the dots); on top the developmental changes in general movements. GM, general movements; PMA, postmenstrual age; CA, corrected age.…”
Section: Typical General Movement Developmentmentioning
confidence: 99%
“…We propose that Smad4 mediated signaling may modulate the required gene expression and chromatin rearrangements to complete VSNs maturation. Proteins of the Nrxn1 family undergo dynamic expression as neurons mature during development (Harkin et al, 2017). Based on our findings in OMPCre +/-/Smad4 flox/flox (cKO) mutants, we speculate that changes in Nrx1 expression arise from an overall compromised maturation rather than a direct Smad4 dependent regulation.…”
Section: Discussionmentioning
confidence: 67%